Cattle Zoonotic and Non-Zoonotic Tick-Borne Pathogens in Europe—A Retrospective Analysis of the Past 15 Years - Diana Hoffman; Ioan Cristian Dreghiciu; Ion Oprescu; Mirela Imre; Tiana Florea; Anamaria Plesko; Sorin Morariu; Marius Stelian Ilie (Animals)
Vector-borne diseases play a significant role in veterinary health, impacting both wild and domestic animals and posing a major constraint on the development of animal husbandry worldwide. The current study aimed to highlight some of the factors involved in the appearance and dissemination of these emerging and re-emerging diseases, as well as the prevalence rate of certain species of pathogens, in cattle throughout Europe. Considering the complexity of vector–host systems, ticks can be mentioned as the first and most common vector involved in the transmission of pathogens in cattle. The highest prevalence was reported for two vector species: Ixodes ricinus and Haemaphysalis punctata. Another factor that contributes to the rapid identification of these diseases is the employed diagnostic method; thus, the most frequently employed techniques in Europe are: PCR, ELISA, and phylogenetic analysis of sequences. The prevalence of tick-borne infections in cattle is continuously increasing. The most frequent associations are Anaplasma spp., Babesia spp., Theileria spp., and Borrelia burgdorferi. Overall, this study highlights a rising occurrence and prevalence of vector-borne diseases in European cattle, underscoring the need for thorough monitoring of farms and vector hotspots—ideally within a “One Health” framework.